Initial status and 3-month results relating to the use of biodegradable nitride iron stents in children and the evaluation of right ventricular function - Sun, Ling; Li, Jun-jie; Xu, Yu-kai; Xie, Yu-mei; Wang, Shu-shui; Zhang, Zhi-wei (Frontiers in Cardiovascular Medicine, 2022)
Background Pulmonary artery stenosis is often associated with congenital heart disease. The aim of the study was to evaluate the efficacy and safety of stenting for branch pulmonary artery stenosis using a biodegradable nitride iron stent (IBS® Angel™) and right ventricular systolic and diastolic function. Methods From July 2021 to February 2022, a total of 11 cases (ages ranged from 36 to 86 months old) were included in this pre and post-intervention, prospective, cohort and preclinical study. All cases underwent transthoracic echocardiographic (TTE), chest radiography, along with computed tomography (256-slice scanner, multiple-detector) and right heart catheterization. Different types of biodegradable nitride iron stents were implanted. TTE was performed serially 1 day, 1 month and 3 months after the procedure to evaluate the rate of restenosis and right ventricular function. Results Stenting was successful in 11 patients. There were no major adverse cardiovascular events related to the device or to the procedure. Blood perfusion in the branch pulmonary artery was improved immediately. At follow-up, there was no significant restenosis that required re-intervention. None of the patients suffered from in-stent thrombosis, vascular embolism, stent displacement or heart failure. Compared with normal values, there were statistical with regards to FAC, E/A and E′/A′. Furthermore, we found that TAPSE correlated significantly with pulsed Doppler S wave (p = 0.008) and left ventricular ejection fraction (p < 0.01). The early trans-tricuspid inflow velocities E/E′ (tissue doppler at the lateral tricuspid annulus) correlated significantly with E′/A′ (p = 0.009). FAC and E′/A′ were statistically different from those prior to stenting (p = 0.041 and p = 0.035) when tested one month postoperatively. At three months postoperatively, only E/A showed a statistical difference (p = 0.015). Conclusion Our analysis suggests that biodegradable nitride iron stents are feasible, safe, and effective in children. Some small improvements were observed in right ventricular systolic and diastolic function after successful transcatheter intervention, although change was not statistically significant due to the small sample number. (A clinical Trial to Evaluate the Safety and Efficacy of IBS Angel in Patients With Pulmonary Artery Stenosis (IRIS); NCT04973540).